GPR55: a new promising target for metabolism?. (April 2017) - Tudurí, Eva; Imbernon, Monica; Hernández-Bautista, Rene Javier; Tojo, Marta; Fernø, Johan; Diéguez, Carlos; Nogueiras, Rubén
Abstract : GPR55 is a G-protein-coupled receptor (GPCR) that has been identified as a new cannabinoid receptor. Given the wide localization of GPR55 in brain and peripheral tissues, this receptor has emerged as a regulator of multiple biological actions. Lysophosphatidylinositol (LPI) is generally accepted as the endogenous ligand of GPR55. In this review, we will focus on the role of GPR55 in energy balance and glucose metabolism. We will summarize its actions on feeding, nutrient partitioning, gastrointestinal motility and insulin secretion in preclinical models and the scarce data available in humans. The potential of GPR55 to become a new pharmaceutical target to treat obesity and type 2 diabetes, as well as the foreseeing difficulties are also discussed.